2014
DOI: 10.4236/jtr.2014.24022
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Hemoptysis in Pulmonary Tuberculosis Patients from Southern China: A Retrospective Study

Abstract: Clinical characteristics of tuberculosis (TB) patients from southern China with pulmonary tuberculosis hemoptysis (PTH) were analyzed retrospectively in order to improve the diagnosis of TB, reduce mortality and prevent the transmission of TB. A total of 1227 cases of pulmonary TB patients hospitalized in the Third Affiliated Hospital of Sun Yat-sen University and Guangzhou Chest Hospital from January to December of 2011 were analyzed retrospectively. 1) The male/female ratio of the 1227 tuberculosis cases was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
1
0
3
Order By: Relevance
“…Shouyong Tan et al observed haemoptysis in 32.8% of PTB in adult population. 16 In our study 2.5% had haemoptysis. Studies quoting incidence of these complications in paediatric DRTB patients are lacking.…”
Section: Discussionsupporting
confidence: 46%
“…Shouyong Tan et al observed haemoptysis in 32.8% of PTB in adult population. 16 In our study 2.5% had haemoptysis. Studies quoting incidence of these complications in paediatric DRTB patients are lacking.…”
Section: Discussionsupporting
confidence: 46%
“…En nuestra serie, el 88% de casos y 23% de controles tuvieron anomalías radiológicas o tomográficas; según el análisis de regresión logística, estos pacientes tuvieron alrededor de 15 veces mayor riesgo de presentar hemoptisis, siendo mayor la probabilidad de sangrado en las bronquiectasias (OR: 16,9 IC: 6,2 -45,8) y cavitaciones (OR: 7,9 IC: 3,2 -19,2), resultado similar a lo reportado por Tan y Parmasivan quienes encontraron una mayor proporción de hemoptisis en pacientes con lesiones cavitarias (19,20) .…”
Section: Discussionunclassified
“…Ukuran partikel yang biasa digunakan di BAE adalah 300-500mikron. 10,11 BAE sangat efektif dalam mengendalikan hemoptisis akut sekitar 73-98% tanpa kekambuhan. Kateterisasi yang selektif dan komplit embolisasi berpengaruh terhadap tingkat keberhasilan.…”
Section: Patogenesis Hemoptisisunclassified
“…10-52% tingkat kekambuhan tergantung pada beberapa faktor termasuk kondisi penyakit primer dan ketepatan prosedur. 10,11 Komplikasi tindakan BAE ini yang paling sering dikeluhkan adalah nyeri dada. Disfagia bisa terjadi pada embolisasi cabang esophagus dan biasanya sembuh dengan sendirinya.…”
Section: Patogenesis Hemoptisisunclassified